Topiramate Monotherapy in Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs)
The dosing, effectiveness, patient characteristics predictive of effectiveness, and safety of topiramate monotherapy in treatment of epilepsy were evaluated in a 6-month, multicenter, open-label study at UCLA School of Medicine, Mattel Children's Hospital, Los Angeles; and University of Miami School of Medicine, FL.